ANALISIS LAPORAN KEUANGAN DEBITUR SEBAGAI BAHAN PERTIMBANGAN PEMBERIAN KREDIT PADA PT BANK SYARIAH MANDIRI CABANG MAROS - Supriadi, Supriadi; Hr, Agus Salim (Universitas Muhammadiyah Makassar, 2018)
This research was conducted at PT Bank Syariah Mandiri, Maros Branch. This study aims to determine the application of financial statement analysis as a material for consideration of credit. In this study, the author is more specialized in Micro Financing (short-term credit) that uses a murabahah financing system. Data in the form of financial statements and data obtained in written form in the form of a general description of the company, namely data collection through direct interviews in the Accounting, Marketing, and HR sections, which are related to the problems examined at PT. Bank Syariah Mandiri Branch Maros. The results of the study concluded, that the debtor's financial statements are influential as material for consideration of giving credit to PT. Bank Syariah Mandiri Branch Maros.